Youth physical activity and sedentary behavior challenges and solutions - Biddle, Stuart; Smith, Alan L. 1968- (Champaign, IL Human Kinetics, 2008)
As interest in the public health challenge of youth inactivity increases, the ambitious Youth Physical Activity and Sedentary Behavior sets a standard for addressing a problem with worldwide implications. Drawing on the contributions of a diverse group of international experts, this reference challenges professionals, researchers, and students to implement new solutions and further their research and work. No other text addresses the causes, contributing factors, and fundamental issues in dealing with youth physical activity with such depth or comprehensive coverage. Using a multidisciplinary approach, Youth Physical Activity and Sedentary Behavior breaks away from traditional thinking that places activity and sedentary behavior on a single continuum, which may limit progress in addressing youth inactivity. Instead, the authors encourage readers to focus on how sedentary and physically active behaviors coexist and consider how the two behaviors may have different determinants. In doing so, the text also considers developmental features such as maturation, ethnicity, environment, and genetics across both childhood (through age 12) and adolescence (the teen years). By looking at a variety of psychosocial and epidemiological factors, the authors set the stage for a critical analysis of beliefs and views at a time when many assumptions are taken for granted. This book is organized in three parts that build on one another to deepen readers' understanding of this complex problem. This text begins by addressing the fundamental issues and assumptions pertaining to youth physical activity and sedentary behavior, covering such topics as measurement of the behavior in question, health outcomes, concepts, and trends in a public health context. Once readers have grasped this foundational knowledge, they advance to part II for a comprehensive account of personal factors likely to be associated with the problem. Part III moves beyond the individual into the wider social and contextual aspects of physically active and sedentary living in young people. Through this concluding part, readers gain the latest thinking on how parents, peers, schools, organized sport, and related factors link to youth physical activity and sedentary behavior. Each chapter presents the latest theory and research, real-world approaches to implementation, and background information to encourage discussion and future directions in national policy making. Youth Physical Activity and Sedentary Behavior also contains the following features that add to an unprecedented learning experience: An at-a-glance look at why and how research can be used in the real world helps researchers relate their work to overall solutions; Coverage of more issues related to this subject than are available in any other reference makes this a one-stop resource; Internationally respected foreword writer, editors, and contributors provide a cross-disciplinary perspective valuable for putting solutions into a wider context; Applications for Professionals boxes and Applications for Researchers boxes at the end of each chapter provide practical suggestions for implementing solutions. Youth Physical Activity and Sedentary Behavior: Challenges and Solutions considers current research about youth physical activity and sedentary behavior across a range of personal factors as well as cultural and social influences. The text communicates the knowledge base on developmental, economic, psychological, and social factors related to youth physical activity and sedentary behavior and provides an overview of youth-specific approaches to addressing the problem of inactivity among youth.
Part I. Conceptualization of Youth Physical Activity and Sedentary Behavior -- Chapter 1. Definitions and Measurement / Simon J. Marshall and Gregory J. Welk -- Chapter 2. Youth Health Outcomes / David J. Stensel, Trish Gorely, and Stuart J.H. Biddle -- Chapter 3. A Sociohistorical Analysis of U.S. Youth Physical Activity and Sedentary Behavior / Mary McElroy -- Chapter 4. Conceptual Perspectives / Claudio R. Nigg and Raheem J. Paxton -- Chapter 5. "Couch Potatoes" and "Wind-Up Dolls"? A Critical Assessment of the Ethics of Youth Physical Activity Research / Michael Gard -- Part II. Developmental and Psychological Factors in Youth Physical Activity and Sedentary Behavior -- Chapter 6. Biocultural Factors in Developing Physical Activity Levels / Robert M. Malina -- Chapter 7. Youth Attitudes / Martin S. Hagger and Nikos L.D. Chatzisarantis -- Chapter 8. Motivational Characteristics / Stuart J.H. Biddle, Darren C. Treasure, and C.K. John Wang -- Chapter 9. The Role of the Self / Peter R.E. Crocker, Kent C. Kowalski, and Valerie Hadd -- Chapter 10. Youth With Movement Difficulties / Janice Causgrove Dunn and Donna L. Goodwin -- Part III. Social and Contextual Factors in Youth Physical Activity and Sedentary Behavior -- Chapter 11. The Family / Brian E. Saelens and Jacqueline Kerr -- Chapter 12. Peers / Alan L. Smith and Meghan H. McDonough -- Chapter 13. Physical Activity Levels During the School Day / Gareth Stratton, Stuart J. Fairclough, and Nicola D. Ridgers -- Chapter 14. Organized Sport and Physical Activity Promotion / Robert J. Brustad, Runar Vilhjalmsson, and Antonio Manuel Fonseca -- Chapter 15. Community Out-of-School Physical Activity Promotion / David A. Dzewaltowski -- Chapter 16. Living Environments / Jo Salmon, John C. Spence, Anna Timperio, and Nicoleta Cutumisu -- Chapter 17. Economic Principles / Chad D. Meyerhoefer -- Chapter 18. Culturally Appropriate Research and Interventions / Suzanna M. Martinez, Elva M. Arredondo, Guadalupe X. Ayala, and John P. Elder.
Includes bibliographical references
Keywords: Health behavior in adolescence; Exercise -- Psychological aspect; Obesity in adolescence -- Prevention